(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on profit growth in tobacco sub-sector companies listed on the Indonesia Stock Exchange (IDX). The study employed a quantitative approach with an associative research design. The sample consisted of four tobacco sub-sector companies, namely PT Hanjaya Mandala Sampoerna Tbk (HMSP), PT Gudang Garam Tbk (GGRM), PT Wismilak Inti Makmur Tbk (WIIM), and PT Indonesian Tobacco Tbk (ITIC) during the 2020–2023 period, resulting in 16 observations. The sampling technique used was purposive sampling. Data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that, partially, the Current Ratio has a significant effect on profit growth, while the Debt to Equity Ratio has no significant effect on profit growth. Simultaneously, the Current Ratio and Debt to Equity Ratio have a significant effect on profit growth. These findings imply that a company’s ability to meet its short-term obligations and manage its capital structure collectively contributes to improving profit growth